Bridging the Gap: An Investigation of Students' needs and Teacher Readiness in English teaching for Business Purpose - Jia, Wen; Zhao, Yaling (Universitas PGRI Sumatera Barat, 2024)
This study is conduced based on the new liberal arts research project in University A, and this study tries to explore students’ actual needs and investigating the preparation of conducting the English teaching for business purpose. The mixed research method, including both quantitative and qualitative method, is used in this research. A semi-structured interview outline and a 5-point Likert scale are used as the research instruments. 5 students are invited to do the interview, to further understand their actual needs towards teaching English with a business purpose. 98 participants including teachers, experts and education administrators are invited to conduct the questionnaire survey to explore the preparation of conducting the English teaching for business purpose. The results show that all the students are highly willing to learn English for business purposes, as they believe learning English for business purposes can contribute to future career development, enhance the pertinence of English learning and expand the depth of professional learning. What’ more, the teaching policy for conducting the English teaching for business purpose is well-prepared, but requirements like teaching materials, the arrangement of the course structure, teacher competence, and evaluation system are need for further improvement.